2021
DOI: 10.1021/acs.jcim.1c00692
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Modeling Based on Conformation Ensembles Using a Multi-Instance Learning Approach

Abstract: Modern QSAR approaches have wide practical applications in drug discovery for designing potentially bioactive molecules. If such models are based on the use of 2D descriptors, important information contained in the spatial structures of molecules is lost. The major problem in constructing models using 3D descriptors is the choice of a putative bioactive conformation, which affects the predictive performance. The multi-instance (MI) learning approach considering multiple conformations in model training could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…46 Accordingly, each step during training, we randomly oriented voxel grids, and for the testing, we averaged the predicted retention times over 24 possible orientations of the input voxel grid. 47 We observed $10(1.6%) seconds improvement in the RT prediction due to random orientation during training and $1.5(0.3%) seconds additional improvement due to the averaging over the 24 predictions corresponding to different grid orientations. To evaluate the robustness with respect to the different conformations of a molecule, we calculated the normalized standard deviation from the predictions obtained for four different conformers of each molecule m in the train and test sets:…”
Section: Neural Network Architecturementioning
confidence: 72%
“…46 Accordingly, each step during training, we randomly oriented voxel grids, and for the testing, we averaged the predicted retention times over 24 possible orientations of the input voxel grid. 47 We observed $10(1.6%) seconds improvement in the RT prediction due to random orientation during training and $1.5(0.3%) seconds additional improvement due to the averaging over the 24 predictions corresponding to different grid orientations. To evaluate the robustness with respect to the different conformations of a molecule, we calculated the normalized standard deviation from the predictions obtained for four different conformers of each molecule m in the train and test sets:…”
Section: Neural Network Architecturementioning
confidence: 72%
“…Nevertheless, there is growing evidence that the use of descriptors incorporating information on the 3D geometries can improve the accuracy of QSPR models, especially for difficult cases that involve very flexible molecules, , as well as for data analytics approaches for materials informatics . One of the core challenges in these efforts is the determination of the conformer geometries that should be used to evaluate the 3D descriptors, an operation for which several strategies have been explored to enhance the accuracy of QSPR models. , As we briefly discussed in section , one of the most promising research directions involves combining the high fidelity of density-based representations with a well-principled construction of ensembles of features. This is still a very active subject of research, with very encouraging results having been recently demonstrated for the prediction of the solubility of small molecules, the computational screening for antiviral drugs, and the prediction of enantioselectivity of organocatalysts …”
Section: Applications and Current Trendsmentioning
confidence: 99%
“…However, it has been debated whether a single conformation or even the method for selection of relevant conformations would provide reliable three-dimensional information 5 ; therefore, a multiinstance learning approach has been proposed. 6,7 In turn, our question goes beyond this: which relevant conformational information do the 3D methods provide that 2D approaches should inform? Multivariate image analysis applied to quantitative structureactivity relationships (MIA-QSAR) is an essentially 2D-QSAR technique, in which the MIA molecular descriptors correspond to pixels of chemical structure images plotted in a blackboard.…”
Section: Introductionmentioning
confidence: 99%
“…According to these methods, the molecules of a data set are placed inside a three‐dimensional lattice and the fields (e.g., steric and electrostatic) are sampled at the intersections of this grid box. However, it has been debated whether a single conformation or even the method for selection of relevant conformations would provide reliable three‐dimensional information 5 ; therefore, a multi‐instance learning approach has been proposed 6,7 . In turn, our question goes beyond this: which relevant conformational information do the 3D methods provide that 2D approaches should inform?…”
Section: Introductionmentioning
confidence: 99%